2008
DOI: 10.1243/09544062jmes787
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effect of the gap values between the overlap portions of the spot-welded pieces on fatigue life

Abstract: In this study, the effect of the space or gap values — between the overlap portions of the spot welded specimens — which is especially important for spot-welded joints subjected to uniaxial in-plane loads, on fatigue life are investigated. In order to do these investigations, a computer programme is developed using ANSYS (version-10) finite-element programme. Numerical results based on the developed computer programme are compared with the experimental results conducted by Sheppard for the validation of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The influence of these factors on the fatigue behavior of spot welded joints made of AHSS has not been sufficiently taken into account. FE‐simulation as well as experimental investigation of spot welded structures with gaps of up to 0.2 mm have shown that the amount of stress near the notch root of the nugget increased, and this effect caused slightly lower fatigue strength 7, 8. Despite the reported observations there seems to be a lack of systematic studies especially for gap sizes between 1 and 4 mm which generally can happen in body shell mass production.…”
Section: Introductionmentioning
confidence: 98%
“…The influence of these factors on the fatigue behavior of spot welded joints made of AHSS has not been sufficiently taken into account. FE‐simulation as well as experimental investigation of spot welded structures with gaps of up to 0.2 mm have shown that the amount of stress near the notch root of the nugget increased, and this effect caused slightly lower fatigue strength 7, 8. Despite the reported observations there seems to be a lack of systematic studies especially for gap sizes between 1 and 4 mm which generally can happen in body shell mass production.…”
Section: Introductionmentioning
confidence: 98%
“…All these analysis have been applied in specific standard test samples like tensile shear (TS), modified tensile shear (MTS), coach peel (CP), and modified coach peel (MCP). In this study, especially tensile shear, 111 (TS), modified tensile shear, 13,6,8 (MTS) and lap shear type 1214 samples were reviewed in terms of predicting the fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…Spot welding technology has been widely used in various industrial fields, more so than other joining methods such as laser welding and friction stir welding, because it has the advantages of high workability, low cost and ease of automation. Spot welding accounts for approximately 90% of sheet metal assemblies in the automobile industry . This technology therefore plays an important role in the joining of thin structures.…”
Section: Introductionmentioning
confidence: 99%
“…Spot welding accounts for approximately 90% of sheet metal assemblies in the automobile industry. 10 This technology therefore plays an important role in the joining of thin structures.…”
Section: Introductionmentioning
confidence: 99%